Postoperative paralytic ileus following debulking surgery in ovarian cancer patients - Egger, Eva K.; Merker, Freya; Ralser, Damian J.; Marinova, Milka; Vilz, Tim O.; Matthaei, Hanno; Hilbert, Tobias; Mustea, Alexander (Frontiers in Surgery, 2022)
Aim This study aims to evaluate the incidence of postoperative ileus (POI) following cytoreductive surgery in epithelial ovarian cancer (EOC) patients and its impact on anastomotic leakage occurrence and postoperative complications. Methods A total of 357 surgeries were performed on 346 ovarian cancer patients between 1/2010 and 12/2020 at our institution. The postoperative course regarding paralytic ileus, anastomotic leakage, and postoperative complications was analyzed by Fisher's exact test and through ordinal logistic regression. Results A total of 233 patients (65.3%) returned to normal gastrointestinal functions within 3 days after surgery. A total of 123 patients (34.5%) developed POI. There were 199 anastomoses in 165 patients and 24 leakages (12.1%). Postoperative antibiotics (p 0.001), stoma creation (p 0.0001), and early start of laxatives (p 0.0048) significantly decreased POI, while anastomoses in general (p 0.0465) and especially low anastomoses (p 0.0143) showed increased POI rates. Intraoperative positive fluid excess >5,000 cc was associated with a higher risk for POI (p 0.0063), anastomotic leakage (p 0.0254), and severe complications (p 0.0012). Conclusion Postoperative antibiotics, an early start with laxatives, and stoma creation were associated with reduced POI rates. Patients with anastomoses showed an increased risk for POI. Severe complications, anastomotic leakages, and POI were more common in the case of intraoperative fluid balance exceeding 5,000 cc.